Chitosan Na-montmorillonite films incorporated with citric acid for prolonging cherry tomatoes shelf life. (September 2022) - Lai, Yingping; Wang, Weitong; Zhao, Jiajia; Tu, Song; Yin, Yingwu; Ye, Liyi
Abstract: This work aims to develop degradable packaging films based on chitosan (CS) and Na-montmorillonite (MMT). The effect of citric acid (CA) on the properties of prepared films (MCS/CAs) was also investigated. MMT shows excellent compatibility in CS. Results from Fourier transform infrared spectroscopy, scanning electron microscopy, and thermogravimetric analysis indicated an improvement in the structural and thermal properties of the films after incorporating MMT into the CS matrix. Despite the reduced tensile strength, the composite films with CA loaded exhibited better swelling resistance and higher elongation at break (68%). MCS/CA-c (loaded with 80% CA) was employed to package cherry tomatoes so as to improve its conservation. Results showed improved physical/chemical properties (weight loss ratio, total soluble solids, titratable acidity, and ascorbic acid) of wrapped cherry tomatoes. Therefore, results reveal the potential of MCS/CAs films as degradable packaging material. Graphical Abstract: ga1 Highlights: Chitosan-based films (MCS/CA) with critic acid cross-linking and clay were prepared. Citric acid (CA) can improve the dispersion of montmorillonite. The elongation at break and thermal performance of MCS/CA films were enhanced. The prepared films can extend the shelf life of cherry tomatoes.